Strategi Komunikasi Persuasif Fasilitator Pada Anggota Sekolah Pensiunan Aqua Lestari (SPENA) Desa Karangjati Kecamatan Pandaan Kabupaten Pasuruan - Misbahul Ulum (Brand Communication, 2023)
The Pension School in Karangjati Pandaan Village is a program that aims to minimize Post Powersyndrome in a retiree. This study aims to determine the persuasive communication strategy applied by the facilitator to SPENA participants, the method used for this research is a persuasive communication model using the AIDDA formula, namely, attention, interest, desire, decision. decision), action (action) as the framework of the argument. This research produces information that, the concept of Attention, namely the facilitator gathers retirees with the same status and builds social networks, the concept of Interest, namely the facilitator strives for retired participants to practice in real terms in the facilities that have been provided. The concept of Desire is that the facilitator socializes the results of the FGDs that have been mutually agreed upon so that retirees have a sense of responsibility for the decisions that have been taken. The Decision concept, namely the facilitator provides verbal and non-verbal support to retirees from a predetermined program, while the Action concept, namely retirement school activities consisting of: socialization, FGD, comparative studies, pensioners screening, school curriculum, and field practice forms of field practice namely: agriculture, duck and goat farming.